RELATIONSHIP BETWEEN EDUCATIONAL DECISION MAKING ABILITY IN BIOLOGICAL AND PERSONALITY (BIG FIVE PERSONALITY) WITH COGNITIVE ABILITY - Gumelar, Agung; Rusdi, Rusdi; Sukmawati, Dalia (Unnes Science Education Journal, 2018)
This study aims to analyze the relationship between decision making abilities and cognitive abilities, personality (big five personality) with cognitive ability, and decision making ability and personality (big five personality) together with cognitive abilities. This research was conducted in the State High School of Pandeglang Regency, Banten Province with a sample of 45 educators. This study uses a quantitative approach, descriptive method with correlational techniques. The results of this study are based on research data analysis using a regression model with a significance level (Î± = 0.05) and a correlation coefficient test with the Pearson Product Moment test (Î± = 0.05). The results of the analysis show that there is a positive relationship between decision making ability and cognitive abilities, there is a positive relationship between personality (big five personality) and cognitive ability and there is a positive relationship between decision making ability and big five personality together with the ability cognitive.